PERANCANGAN DAN PEMBUATAN JIG AND FIXTURE DENGAN MESIN COMPUTER NUMERICAL CONTROL (CNC) MILLING DI PT PRIMA ANUGRAH TEKNIK - Agus Widodo; Joko Prasetyo (INKOFAR, 2025)
The manufacturing industry has a strategic role in driving national economic growth through increased added value and export contributions. One of the companies engaged in this sector is PT Prima Anugrah Teknik, which produces NJUT6 Knuckle Joint components from stainless steel using CNC Milling machines and hydraulic ramps. In May, the company targeted production of 520 units, but was only able to produce 416 units. The low production output was caused by an inefficient machining process due to the use of conventional clamping tools that often caused dimensional inaccuracies and product defects. This research aims to improve production efficiency and quality through the design and implementation of jigs and fixtures as aids in the machining process. The design process begins with design creation using SolidWorks 2018 software, followed by machining programming using Mastercam and Cimco, thorough assembly of components through the welding process, and direct testing on a CNC Milling machine. The results showed a significant increase in production efficiency, where the machining time for every 4 units of NJUT6 could be shortened to 18 minutes. In addition, the use of jigs and fixtures was able to reduce defect rates, improve dimensional precision, and simplify the installation process. The implications of this research show that the development of production aids such as jigs and fixtures can be an effective solution in overcoming efficiency problems in the manufacturing industry, and can be replicated on other production lines to increase productivity and competitiveness.